Law Students' Attitudes to Education: Pointers to Depression In the Legal Academy and the Profession? - Massimilliano Tani; Prue Vines (Legal Education Review)
This article focuses on what is likely the most common form of simulation used in law schools, the moot. It discusses concerns about the use of moots in some law schools in three jurisdictions (Australia, the United States and the United Kingdom). The concerns are divided into three categories: those intrinsic to “the traditional moot”, those that arise because of the way in which moots are incorporated into the law curriculum, and those that are a product of the nature of moots and the way in which we integrate them. The article suggests a sustainable affordable way in which to address these concerns. The solution proposed consists of two initiatives. First, it is suggested that the traditional moot be replaced with a variety of simulations that make more effective use of experiential learning than does the traditional moot. Second, it is suggested that simulations such as the ones described in the article be integrated into the curriculum by way of a “skills, ethics and values matrix”. The article draws on literature from a number of jurisdictions and on the results of a longitudinal study of the efforts of one law school in Australia, Bond University School of Law, to improve teaching and learning in advocacy, ethics and values in the law curriculum.